The Regulation of Directors’ Remuneration: An Overview of the Malaysian Position – Sujata Balan - Balan, Sujata (Journal of Malaysian and Comparative Law, 2017)
This article discusses the laws and legal principles that govern the subject of directors’ remuneration in Malaysia. It examines the extent to which the Malaysian courts, companies legislation and shareholders of a company have control over directors’ remuneration and access to information concerning such remuneration. Importantly, this article will highlight and discuss the significant changes brought about by the Companies Act 2016 on this subject. Chief among these are the introduction of new provisions allowing members of public companies to inspect service contracts of directors and a new mandatory provision that requires the remuneration of directors in public companies to be approved by the members in a general meeting of the company.